Telecommunications — International trade and US trade policy - Thomas Schnöring (Intereconomics, 1986)
Deregulation of the US telecommunications market—by far the largest in the world, accounting for 40% of the world market—has led to a rapid increase in imports, so that the United States is now pressing for “reciprocal” changes in other countries' telecommunications markets. The Telecommunications Trade Act of 1986 threatens countries with retaliatory measures if they fail to shape their telecommunications policies in accordance with the very precise requirements set out in the trade policy objectives. This raises the question of their sovereign powers to determine policy in the telecommunications field.
Keywords: 330